Fungal endophytes from the leaves and twigs of Quercus ilex L. from England, Majorca and Switzerland (New Phytologist, 1994)
Leaves of Quercus ilex taken from sites in England, Majorca and Switzerland have been studied to detect the influence of the geographic position of the host within and outside its native range on the composition of its endophytic fungal assemblages. Samples of stem tissue of Q. ilex collected from the Swiss trees were also studied to confirm tissue-specific differences. Sixty different fungal taxa were isolated, but only 28 were frequent. Of the total number of isolates from the leaves from the Swiss, British and Spanish sites 87%, 31% and 63%, respectively, were coelomycetes. Four species of Phomopsis, which includes Phyllosticta ilicina (=Phomopsis ilicina v. d. Aa, ined.), were the most frequent endophytes of leaves and were either absent or rare in the twig units. Two distinct kinds of sterile mycelia were common in twigs. Swiss and Spanish trees possessed fungal assemblages distinct from those present in Britain. Naturalized stands were distinguished from native stands by the presence of rather cosmopolitan and non-specific fungal taxa, rare or absent in the samples collected in the native stands. Samples derived from the native stands were colonized by more host-specific fungi. The relative frequency of two sterile mycelia in the Swiss and Spanish sites determined their separation. Phyllosticta (Phomopsis) ilicina, the most numerous leaf colonizer, was virtually absent from the bark and the xylem. The frequent occurrence of coelomycetes as endophytes of woody trees is briefly discussed.